(untitled) - Sanders, Jeremy K. M (Oxford, UK, 1993)
This book provides a non-mathematical, descriptive approach to modern NMR spectroscopy, taking examples from organic, inorganic, and biological chemistry. It also contains much practical advice about the acquisition and use of spectra. Starting from the simple 'one pulse' sequence, the text employs a 'building block' approach to lead naturally to multiple pulse and two-dimensional NMR. Spectra of readily available compounds illustrate each technique. One- and two-dimensional methods are integrated in three chapters which show how to solve problems by making connections between spins through bonds, through space, or through exchange. There are also chapters on spectrum editing and solids. The final chapter contains a case history which attempts to weave the many strands of the text into a coherent strategy
Keywords: Nuclear magnetic resonance spectroscopy,Phổ học cộng hưởng từ hạt nhân